Penerapan Good Corporate Governance, Komitmen Organisasi, Gaya Kepemimpinan Transformasional dan Kinerja Karyawan Lembaga Perkreditan Desa - Diah Cantika Wibawa, Ni Luh Putu; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi; Vol 31 No 3 (2021)DO - 10.24843/EJA.2021.v31.i03.p06, 2021)
The purpose of this study was to determine the effect of Good Corporate Governance, organizational commitment, leadership style on the performance of rural credit employee institutions. The population in this study were 122 LPDs in Badung Regency. The analysis technique used was multiple linear regression. Based on the established criteria, 55 LPD samples were taken in Badung Regency. The results of this study indicate that good corporate governance, organizational commitment and transformational leadership style have a positive effect on the performance of LPD employees in Badung Regency.  Keywords: Good Corporate Governance; Organizational Commitment; Leadership Style; Employee Performance.